Smart'13 : smart materials and structures : selected, peer reviewed papers from the VI Eccomas Thematic Conference on Smart Structures and Materials (SMART'13), June 24-26, 2013, Torino, Italy - Carrera, Erasmo (Advanced materials research, 2013)
Smart materials and structures is an area of technology which has been around for approximately 30 years or more where materials and structures are augmented by sensing and actuation functionality, and those functions are combined with control elements, all becoming an integral part of the materials and structures considered. This book collects selected Plenary Lectures and Key-Note Lectures from the VI Eccomas Thematic Conference on Smart Structures and Materials (SMART'13), June 24-26, 2013, Torino, Italy. The conference deals with materials and structures that are augmented with sensing and.